2022
DOI: 10.1590/1980-265x-tce-2022-0155en
|View full text |Cite
|
Sign up to set email alerts
|

Riverside Men's Knowledge and Ways of Acting Regarding Condom Use

Abstract: Objective to analyze riverside men's knowledge and ways of acting regarding condom use, based on the social representations about the device. Method a qualitative study anchored in the Theory of Social Representations and conducted with 21 riverside men from the São Carlos do Jamari community, Porto Velho, Rondônia, Brazil. Data collection was performed between January and July 2019 by means of an interview with a semi-structured questionnaire. For data processing, the Statistical Package for the Social Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have shown that the syphilis epidemic and its repercussions differ according to populations [ 4 – 10 ]. Identifying and recognizing the differences and specificities of this process becomes essential in the design and implementation of policies aimed at assisting groups most vulnerable to syphilis [ 11 13 ]. In rural communities, the prevalence of syphilis in adults ranged from 0.2% among women in rural Nepal [ 5 ] to 16% among men living with HIV in rural Uganda [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the syphilis epidemic and its repercussions differ according to populations [ 4 – 10 ]. Identifying and recognizing the differences and specificities of this process becomes essential in the design and implementation of policies aimed at assisting groups most vulnerable to syphilis [ 11 13 ]. In rural communities, the prevalence of syphilis in adults ranged from 0.2% among women in rural Nepal [ 5 ] to 16% among men living with HIV in rural Uganda [ 8 ].…”
Section: Introductionmentioning
confidence: 99%